Outcomes from an international multicenter registry of patients with acute gastrointestinal bleeding undergoing endoscopic treatment with Hemospray. Issue 1 (30th August 2019) - Alzoubaidi, Durayd; Hussein, Mohamed; Rusu, Radu; Napier, Duncan; Dixon, Selena; Rey, Johannes W.; Steinheber, Cora; Jameie‐Oskooei, Sina; Dahan, Martin; Hayee, Bu; Gulati, Shraddha; Despott, Edward; et al.
Abstract : Background and Aim: Acute gastrointestinal bleeding carries poor outcomes unless prompt endoscopic hemostasis is achieved. Mortality in these patients remains significant. Hemospray is a novel intervention that creates a mechanical barrier over bleeding sites. We report the largest dataset of patient outcomes after treatment with Hemospray from an international multicenter registry. Patients and Methods: Prospective data (Jan 2016–May 2018) from 12 centers across Europe were collected. Immediate hemostasis was defined as endoscopic cessation of bleeding within 5 min after application of Hemospray. Rebleeding was defined as subsequent drop in hemoglobin, hematemesis, persistent melena with hemodynamic compromise post‐therapy. Results: Three hundred and fourteen cases were recruited worldwide (231 males, 83 females). Median pretreatment Blatchford score was 11 (IQR: 8–14) and median complete Rockall score (RS) was 7 (IQR: 6–8) for all patients. Peptic ulcer disease (PUD) was the most common pathology (167/314 = 53%) and Forrest Ib the most common bleed type in PUD (100/167 = 60%). 281 patients (89.5%) achieved immediate hemostasis after successful endoscopic therapy with Hemospray. Rebleeding occurred in 29 (10.3%) of the 281 patients who achieved immediate hemostasis. Seven‐day and 30‐day all‐cause mortality were 11.5% (36/314) and 20.1% (63/314), respectively (lower than the predicted rates as per the RS). Similar hemostasis rates were noted in the Hemospray monotherapy (92.4%), combination therapy (88.7%) and rescue therapy (85.5%) groups. Conclusions: These data show high rates of immediate hemostasis overall and in all subgroups. Rebleeding and mortality rates were in keeping/lower than predicted rates.